REPAIR TECHNOLOGY OF THE COMPOSITE WING OF A LIGHT PLANE DAMAGED DURING AN AIRCRAFT CRASH - Andrzej ŚWIĄTONIOWSKI; Janusz SZOSTAK; Dorota CHODOROWSKA (Scientific Journal of Silesian University of Technology. Series Transport)
The increasing use of composite structures in aircraft constructions has made it necessary to develop repair methods that will restore the component’s original design strength without compromising its structural integrity. In this paper, the complex repair technology of the composite wing of a light plane, which was damaged during an aircraft crash, is described. The applied repair scheme should meet all the original design requirements for the plane structure.